Підготовчий єтап до адаптації організації будівництва до євровимог - Тугай, О. А.; Сліпенчук, О. В.; Кухта, К. П. (Ways to Improve Construction Efficiency, 2013)
Offered approach to preparation of building production that adapts him to European requirements and standards. Approach it is suggested to realize within the framework of innovative control system "design and build" and new standards of quality, that embrace all investment cycle - intention, planning, preparation and building. Theoretical and methodical bases of such approach are expounded .